Manokwari Wasti Lake Mangrove Forest Vegetation Structure, West Papua - Semuel Sander Erari; Jan H. Nunaki; Sepus M Fatem (Fakultas Biologi Universitas Gadjah Mada, 2023)
Wasti lake in Manokwari is one of the mangrove forest areas located on the coast of Manokwari and has ecological, economic and socio-cultural potential. Development continues, land conversion for settlement and economic development will have a negative impact on the sustainability of the mangrove ecosystem in Wasti Lake. Thus, this study aims to determine the vegetation structure of the mangrove forest at Telaga Wasti and its ecological potential to prepare teaching materials for ecology courses at the Biology Education Study Program, University of Papua. This research was conducted in May - July 2022. The method used is the line method (transect line) and the quadratic method. Data was collected on plots measuring 20m x 20m for tree vegetation, 10m x 10m for pole vegetation, 5m x 5m for saplings and 2m x 2m for seedlings. The results of data analysis showed that the mangrove vegetation structure consisted of 7 species from 4 families. The highest INP at tree level for both stations was Sonneratia alba, while the highest INP for pole level at station I was Rhizophora stylosa and station II was Sonneratia alba. The highest level of sapling at station I INP was Rhizophora stylosa and at station II the highest INP was R. apiculata. Then the highest INP station I seedling vegetation was R. stylosa and the highest INP Station II was R. apuculata.